THE IMPACT OF SOYBEAN AND CORN INTERCROPPING SYSTEM AND SOIL FERTILITY MANAGEMENT ON SOYBEAN APHID POPULATIONS APHIS GLYCINES (HEMIPTERA: APHIDIDAE) AND SOYBEAN GROWTH PERFORMANCE - Rosma Hasibuan; Jamalam Lumbanraja (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2012)
Agricultural management cropping systems play an important role in affecting a crop plant’s ability to tolerate or resist insect pests. Field studies were conducted to examine the effect of two strategies management systems: fertilizer treatment and intercropping soybean with corn on soybean aphid (Aphis glycines Matsumura) population and soybean growth and yield parameters. The intercropping treatments were: soybean alone; 2:1 soybean/corn intercrop; and 3:1 soybean/corn intercrop. While the soil fertility treatments were the combination of NPK (urea 100 kg ha-1 + SP-36 200 kg ha-1 + KCl 200 kg ha-1) levels, dolomite (4 ton ha-1), compost (10 ton ha-1), and chicken manure (10 ton ha-1). The results of the first study showed that the intercropping soybean with corn significantly reduced the population density of soybean aphids. However, there were no significant effects of intercropping systems on soybean growth (plant height) and yield (number seed per pod and thousand seed weight) performances except on the number of soybean pods per plant. Meanwhile, the result of the second study indicated that soil fertilizer treatments had a significant effect on the soybean plant characteristics: leaf numbers; pod numbers; and plant height. Combining intercropping methods and soil fertilizer management offer an opportunity to protect the soybean plants by natural and sustainable pest management.